RECURSOS BIOGENÉTICOS Y LÓGICAS MERCANTILES: LA EXPERIENCIA COSTARRICENSE - Lizano, Randall Blanco (Universidad de Costa Rica, 2006)
The article analyzes the mercantile logics that justify the appropriation of biogeneticresources in Costa Rica and the consequences on the cultural practices of indigenouscommunities and farmers.